The Theme and Symbolism of the Bridge in European and Serbian Early Modernist Painting - Tubić, Dejan M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
In the period from the late 19th century to the early 20th century, the bridge motif in European and Serbian early modernist painting expanded the visual and symbolic phenomenology of the bridge. Through its architecture and symbolism, the bridge overcomes barriers, leads into the unknown and uncertain, and opens a dialogue between different spaces and times. The bridge is a path that one must cross, yet also return to. It serves as an archetypal representation of connection and separation, permanently present in human morphogenesis. The bridge establishes a correspondence between individuals, nations, cultures, and various confessions.The early modern period introduced innovative aesthetic concepts of representing bridges in painting. One vision is rooted in respecting historicist tradition, with depictions based on ancient, medieval, and modern forms of the bridge. Another early modernist concept of the bridge is founded on critically examining and glorifying the creative and structurally daring forms of contemporary bridges. A third type of bridge in European and global painting reflects the influence of Japanese art on early modernism. A fourth aesthetic approach to the bridge motif during the early modern period emerged in the Balkans, based on the romantic-realist depiction of bridges built during the Ottoman period.An essential aspect of understanding the popularity of the bridge motif in early modernist painting is Japonism. The Romantic fascination with the Orient during early modernism was largely replaced by the discovery of Japanese visual philosophy. French Impressionism played a crucial role in establishing the phenomenology of Japonism within European culture. Claude Monet’s fascination with Japonism is confirmed by the Japanese garden and bridge he built in his own backyard. He painted the Japanese bridge in his garden multiple times, creating an Impressionist series around this identical motif. Vincent van Gogh raised the European and Japanese depictions of bridges to the level of a successful aesthetic symbiosis. Van Gogh’s motifs of Japanese bridges enriched European art, adding complexity both aesthetically and thematically.The Dresden Expressionist group Die Brücke initiated a theoretical discourse on the theme of the bridge, approaching it through a new etymological interpretation. The artists of the Dresden group chose to name their movement The Bridge, as a means to connect with their own foundation. Their idea of the bridge is to establish renewed correspondence with essential, symbolist, and contemplative content.Parallel to the appearance of the bridge motif in German Expressionism, it also became popular in French Fauvism. Representatives of Fauvist painting, aligned with their aesthetic aspirations, established correspondence with the bridge motif. Through intense and ‘wild’ colours, destruction of the figurative and spatial, and without tonal modelling, the Fauvists presented their vision of the bridge.Cubism, like other early modern movements, offered a new reception of the bridge motif on the global art scene. Light, transparent bamboo bridge structures were replaced by heavy, stone arch bridges, with forms based on Cubist shapes such as the cube, cylinder, and pyramid. The bridge motif became prominently featured in Serbian early modernist painting. Many significant Serbian artists of that period painted and photographed bridges. Through their own artistic philosophy and the mimicry of inner content, the bridge motif established itself as a central theme and an important iconographic detail in many canvases of Serbian early modernist painting.There are numerous arguments to suggest that Serbian painting entered the modern era, in part, through the strong reception of the bridge motif. In 1907, Milan Milovanović painted one of the key works of Serbian Impressionism, The Bridge of Emperor Dušan in Skopje. On the canvas, Milovanović depicted the stone arch bridge over the Vardar River. In 1913, Nadežda Petrović, as a wartime nurse and painter, created two striking variants of the Vezir’s Bridge. In the context of the Serbian early modernist reception of European bridge representations, Serbian painting managed to preserve its aesthetic autonomy. Without strong influences from Japonism or modernist metal bridge structures, the Serbian early modernist vision of the bridge is based on historicist tradition, romantic ideas, and authentic interpretations of Orientalism.
Keywords: painting; bridge; Early Modernism; Japonism; Vezir’s bridge